The ubiquitin proteasome system and myocardial ischemia - Calise, Justine; Powell, Saul R. (American journal of physiology. Heart and circulatory physiology, 2013)
The ubiquitin proteasome system (UPS) has been the subject of intensive research over the past 20 years to define its role in normal physiology and in pathophysiology. Many of these studies have focused in on the cardiovascular system and have determined that the UPS becomes dysfunctional in several pathologies such as familial and idiopathic cardiomyopathies, atherosclerosis, and myocardial ischemia. This review presents a synopsis of the literature as it relates to the role of the UPS in myocardial ischemia. Studies have shown that the UPS is dysfunctional during myocardial ischemia, and recent studies have shed some light on possible mechanisms. Other studies have defined a role for the UPS in ischemic preconditioning which is best associated with myocardial ischemia and is thus presented here. Very recent studies have started to define roles for specific proteasome subunits and components of the ubiquitination machinery in various aspects of myocardial ischemia. Lastly, despite the evidence linking myocardial ischemia and proteasome dysfunction, there are continuing suggestions that proteasome inhibitors may be useful to mitigate ischemic injury. This review presents the rationale behind this and discusses both supportive and nonsupportive studies and presents possible future directions that may help in clarifying this controversy.